Психолінгвальні маркери ранніх дисфункційних схем у вчителів із високим ступенем трудоголізму - Onopchenko, Iryna; Orap, Maryna; Mudrak, Ihor; Онопченко, Ірина; Орап, Марина; Мудрак, Ігор (Lesya Ukrainka Eastern European National University, 2019)
This study examines psycholinguistic markers of early maladaptive schemas in teachers with high prevalence of workaholism. The study represents the cross-sectional, betweensubjects design utilizing the independent variables of early maladaptive schemas, psychological wellbeing, daily job satisfaction, satisfaction of marriage and dependent variable of workaholism in teachers. The approval letter to recruit the participants from secondary schools in Volyn Oblast, Ukraine in 2018-2019 academic year was obtained from the Research Ethics Committee at Lesya Ukrainka Eastern European National University. 53 teachers, females (n=50), males (n=3), mean age was 46.47 (SD=10.17), seniority was 24.06 (SD=10.97) were recruited. Young Schema Questionnaire, Version 3 (YSQ – S3), The Workaholism Facet-Based Scale (Shkoler et al., 2018), Satisfaction of Marriage Scale (Stolin et al., 1984), Daily Job Satisfaction Scale методика задоволення щоденною роботою (Loi et al., 2009), Ryff’s Scale of Psychological Well-Being assess workoholism and its relations with well-being and satisfaction in teachers. The results indicate that early maladaptive schemas, psychological well-being, satisfaction of marriage taken together are predictors of workaholism. However, early maladaptive schemas are the only independent significant predictors of workaholism in teachers. The most frequent statements as psycholinguistic markers of developed early maladaptive schemas in teachers with high prevalence of workaholism are examined. The high prevalence of workaholism in teachers is associated with vulnerability to harm or illness; self-sacrifice; unrelenting standards and hypocriticalness; approval and recognition seeking; negativity and punitiveness. The principal implication of this study is that early maladaptive schemas might be examined through psycholinguistic markers represented by frequent verbal statements of teachers with high prevalence of workaholism.У статті відображено результати дослідження психолінгвальних маркерів ранніх дисфункційних схем у вчителів. Дослідження представлене у вигляді багатопланового дослідження із залученням регресійного аналізу, де ранні дисфункційні схеми, психологічне благополуччя, задоволення шлюбом слугують незалежними змінними, а трудоголізм – залежною змінною. Після отримання дозволу від Ради з етики наукових досліджень Східноєвропейського національного університету імені Лесі Українки 53 учителі загальноосвітніх шкіл Волинської області (Україна) взяли участь у дослідженні трудоголізму, серед них 50 жінок, 3 чоловіків, середній вік 46,47 (SD=10,17), стаж роботи 24,06 (SD=10,97). Опитувальник Янга YSQ – S3, шкала трудоголізму (Shkoler et al., 2018), шкала задоволеності шлюбом (Столін, Романова, Бутенко), шкала задоволення щоденною працею (Loi et al., 2009), шкала психологічного благополуччя (Ryff & Keyes, 1995) використовувалися для дослідження трудоголізму та його предикторів у вчителів. Результати засвідчили, що ранні дисфункційні схеми, психологічне благополуччя, задоволеність шлюбом сукупно слугують предикторами трудоголізму у вчителів. Водночас лише ранні дисфункційні схеми є незалежними значущими предикторами трудоголізму. Визначено психолінгвальні маркери ранніх дисфункційних схем, пов’язаних із трудоголізмом. Високорозвинений трудоголізм у вчителів пов’язаний із очікуванням на катастрофу, страхом покарання і негативізмом, уявленням про власну некомпетентність і невдачу, пошуком визнання й високих стандартів. Важливим прикладним висновком дослідження є можливість використання психолінгвістичних маркерів для визначення ранніх дисфункційних схем, пов’язаних із трудоголізмом у вчителів.
Psycholinguistic Markers of Early Maladaptive Schemas in Teachers with High Prevalence of Workaholism
Keywords: трудоголізм вчителів; ранні дисфункційні схеми; психологічне благополуччя; задоволення щоденною працею; задоволення шлюбом; психолінгвальні маркери; workaholism in teachers; early maladaptive schemas; psychological well-being; daily job satisfaction; satisfaction of marriage; psycholinguistic markers